Guidelines for a Nonprint Materials Core in a Learning Resource Program - California Community Colleges, Sacramento. Office of the Chancellor; California Community Colleges, Sacramento. Office of the Chancellor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Learning Resource Programs and the space necessary to house them have been a challenging planning problem in the California community colleges. There have been standards for space utilization of the traditional library since 1966, but these provided for print materials only. The purpose of this report is to provide standards for the Nonprint Materials Core (audiovisual, TV, production services, etc.) when planning and evaluating a Learning Resources Program project for California community colleges. Space requirements will vary with the total anticipated enrollment. Five thousand square feet is the minimum space requirement for institutions with less than 1,000 day-graded students. Methods of computing additional space requirements for colleges with greater than 1,000 students are presented. Also presented are percentage allocations for various aspects of the core (production, housing, maintenance of equipment, staff, and public services/technical processing) which can be used for enrollments up to 9,000. The guidelines were produced through a number of conferences with an ad hoc group and the standards committee. (DC)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Centers; College Libraries; Communications; Educational Resources; Educational Television; Facility Guidelines; Facility Planning; Facility Requirements; Learning Resources Centers; Space Utilization; Two Year Colleges; California; Guides, General